2020
DOI: 10.24967/jmms.v1i04.522
|View full text |Cite
|
Sign up to set email alerts
|

Analisa Komparasi Jumlah Serapan Pembangunan Berdasarkan Aspirasi Masyarakat Melalui Musrenbang Dan Reses

Abstract: Tuntutan penyelenggaraan pemerintah yang demokratis diantaranya adalah dalam proses pembangunan yang partisipatif dan efisien dalam penyelenggaraan sistem pemerintahan dari tingkat yang tertinggi hingga yang terendah. Untuk mengakomodir hal tersebut Pemerintah Pusat merespon situasi ini dilaksanakannya desentralisasi penyelenggaraan pemerintahan secara nyata. Penelitian yang dilakukan berupa studi kasus tentang proses penyusunan APBD Kabupaten Pesawaran Tahun Anggaran dan serapan aspirasi masyarakat melalui me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Studies on recess activities in Indonesia rarely receive attention, some existing studies on recess include a study conducted in Banyuasin Regency which concluded that recess activities carried out by DPRD members in Banyuasin Regency were very effective for proposing citizen programmes [12]. Pujiati [13] conducted research by comparing the level of effectiveness of Musrenbang and Recess carried out in the preparation of the Pesawaran Regency APBD that resulted in 2018 activities proposed through musrenbang can be absorbed as much as 62.3%, while recess is only approximately 37.7%. Badrika and Sulandari [14] who conducted a study on the effectiveness of the implementation of recess for members of the Tabanan Regency DPRD in Bali, showed that it proved to be very effective in terms of community aspiration absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on recess activities in Indonesia rarely receive attention, some existing studies on recess include a study conducted in Banyuasin Regency which concluded that recess activities carried out by DPRD members in Banyuasin Regency were very effective for proposing citizen programmes [12]. Pujiati [13] conducted research by comparing the level of effectiveness of Musrenbang and Recess carried out in the preparation of the Pesawaran Regency APBD that resulted in 2018 activities proposed through musrenbang can be absorbed as much as 62.3%, while recess is only approximately 37.7%. Badrika and Sulandari [14] who conducted a study on the effectiveness of the implementation of recess for members of the Tabanan Regency DPRD in Bali, showed that it proved to be very effective in terms of community aspiration absorption.…”
Section: Introductionmentioning
confidence: 99%